2009
DOI: 10.1038/ijo.2009.161
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of FTO genotype in the development of obesity in Japanese: the J-SHIPP study

Abstract: Objective: Susceptibility of fat mass and obesity-associated (FTO) gene polymorphisms to obesity has been reported in various populations. Polymorphisms in the melanocortin 4 receptor (MC4R) gene were recently explored as another susceptible locus. However, prognostic significance of these genetic variations has not been fully elucidated. Here, we investigated the involvement of FTO rs9939609 and MC4R rs17782313 polymorphisms in the development of obesity. Association with type 2 diabetes mellitus (T2DM) was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 35 publications
5
18
0
2
Order By: Relevance
“…In addition, one article was excluded as it was a review and nine articles were excluded because they investigated the association between the MC4R polymorphism and obesity, obesity-related traits, stroke or polycystic ovary syndrome. Therefore, 13 articles met the primary inclusion criteria, of which one article was excluded because it was a duplicated publication [19] and another article was excluded because it did not provide sufficient data for calculation of an OR with 95% CI [20]. In addition, the nine studies included in the paper by Loos et al [3] were considered as separate studies in the following data analysis.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, one article was excluded as it was a review and nine articles were excluded because they investigated the association between the MC4R polymorphism and obesity, obesity-related traits, stroke or polycystic ovary syndrome. Therefore, 13 articles met the primary inclusion criteria, of which one article was excluded because it was a duplicated publication [19] and another article was excluded because it did not provide sufficient data for calculation of an OR with 95% CI [20]. In addition, the nine studies included in the paper by Loos et al [3] were considered as separate studies in the following data analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The personal health records evaluated at previous medical checkups were obtained from a clinical database administrated by the local city council [12]. For each subject, the oldest data available from 1992 to 1996 were obtained.…”
Section: Methodsmentioning
confidence: 99%
“…In general, studies in populations of East Asian [48,49,50,51,52,53,54,55,56,57,58,59,60,61,62], South Asian [63,64,65] and African origin [66,67,68,69,70,71,72,73], in particular those with larger sample sizes, have found that the FTO locus associates convincingly with BMI and obesity risk, with effect sizes similar to those observed in white European populations. The risk allele frequency of the FTO locus, however, varies substantially: being ∼20% in East Asian populations, ∼30% in South Asians but ∼45% in white Europeans.…”
Section: Gwas and Non-european Populationsmentioning
confidence: 99%
“…Although the risk allele frequency (∼16–20%) in populations of African ancestry was lower, the effect sizes tended to be similar or even somewhat larger than in white Europeans. Studies of populations of East Asian descent, where the risk allele is less frequent (∼19%) than in white Europeans, have not yet found consistent replication of this locus [52,56,58,60,61,76,77]. A meta-analysis of all available data will be needed to confirm or refute association of this locus with obesity susceptibility in these populations.…”
Section: Gwas and Non-european Populationsmentioning
confidence: 99%